Vitamin D and Hemostasis Parameters in Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome Patients with Pulmonary Tuberculosis Coinfections - Erica, Elrica; Sari, Dina Keumala; Siregar, Dewi Indah Sari; Mega, Juli Yosa (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Human Immunodeficiency Virus (HIV)/Acquired Immunodeficiency Syndrome (AIDS) remains one of the most common causes of Vitamin D deficiency and homeostasis disorders due to its progressiveness and complications. AIM: This study aims to determine the relationship of Vitamin D levels with hemostasis in HIV/AIDS patients with and without pulmonary tuberculosis (TB), who were consuming efavirenz (EFV)-based antiretroviral therapy (ART) for <6 months, with or without rifampicin-based antituberculosis treatment. METHODS: 25(OH)D concentration, prothrombin time (PT), and platelet index were measured in HIV/AIDS patients with and without pulmonary TB, who were consuming EFV-based ART for <6 months, with or without rifampicin-based antituberculosis treatment. This study was conducted in the Special Treatment Centers (Pusat Pelayanan Khusus, Pusyansus) Voluntary Counseling and Testing clinic at Rumah Sakit Umum Pusat (RSUP) Haji Adam Malik, Medan, Indonesia, between August and October 2019. RESULTS: We found no significant difference in terms of 25(OH)D concentration, PT, and platelet index between the two groups, except for platelet distribution width (PDW) differs significantly between HIV/AIDS-pulmonary TB group and HIV/AIDS only group (p = 0.026). We observed a significant difference in terms of mean platelet volume and PDW between baseline and after treatment for <6 months (p ≤ 0.05) in the HIV/AIDS-pulmonary TB group and in the HIV/AIDS only group. A significant difference was also observed in terms of platelet count (p = 0.021) before and after EFV-based ART for <6 months p ≤ 0.05) in the HIV/AIDS-pulmonary TB group. CONCLUSION: There is no correlation between 25(OH)D concentration and PT or platelet index in HIV/AIDS patients with and without pulmonary TB who were consuming EFV-based ART- and rifampicin-based antituberculosis for <6 months.